Analisis Rencana Strategi Bisnis berdasarkan Perspektif Balanced Scorecard (BSC) - Katresna Sakalih (Jurnal Riset Ilmu Ekonomi dan Bisnis, 2026)
Abstract. At the moment, hospitals are growing quickly, which is making competition more intense. A provider of healthcare has to deal with this difficulty. The purpose of this study is to identify the best business plan using the four perspectives of the balanced scorecard (BSC) approach. Descriptive qualitative research using a case study methodology is the methodology employed. The research involved several stages of data analysis.IFE (3.47) and EFE (3.61) are the Internal-External (IE) Matrix scores according to the research findings. Strengths (2,78), Weaknesses (0.69), opportunities (2.91), and threats (0.70) are the outcomes of the SWOT. According to the Internal-External (IE) Matrix, the hospital is located in Cell V (Hold and Maintain or Stabilization). Additionally, quadrant 1 (aggressive strategy) has the SWOT matrix. Market and product development using the QSPM matrix method is the selected approach. The four perspectives of the Balanced Scorecard (BSC) are then used to apply the business strategy options. Financial Perspective by optimizing insurance claims and boosting income and financial growth. Customer Perspective, boosting the frequency of visits, and offering unrestricted service access. Internal Business Perspective, strengthening the hospital's reputation, and providing specialized HR. And learning and growth perspective, improving employee performance and abilities. Abstrak. Pertumbuhan rumah sakit saat ini meningkat pesat, sehingga menciptakan persaingan yang semakin ketat. Hal ini merupakan tantangan yang harus dihadapi oleh suatu organisasi rumah sakit. Penelitian ini bertujuan untuk mengetahui strategi bisnis ideal berdasarkan pendekatan empat perspektif balanced scorecard (BSC). Metode penelitian yang digunakan deskriptif kualitatif dengan pendekatan studi kasus. Dalam penelitian ini dilakukan beberapa tahapan analisis data. Hasil penelitian menujukan skoring Matriks Internal Eksternal (IE) IFE (3,47) dan EFE (3,61). Hasil skoring Analisis Matriks SWOT, Kekuatan (2,78), Kelemahan (0,69), Peluang (2,91) dan Ancaman (0,70). Posisi rumah sakit berdasarkan Matriks Internal Eksternal ada pada Sel V (Hold and Maintain atau Stabilisasi). Dan matriks SWOT pada kuadran I (strategi agresif). Strategi yang dipilih yaitu pengembangan pasar dan pengembangan produk. Hasil dari strategi bisnis berdasarkan perspektif Balanced Scorecard yaitu, Persfektif keuangan dengan meningkatakan pendapatan dan pertumbuhan keuangan, serta otimaliasi klaim asuransi. Persfektif Pelanggan, meningkatkan angka kunjungan dan menyedikakan keterbukaan akses layanan. Persfektif Bisnis Internal, melengkapi SDM Spesialis dan meningkatkan brand image rumah sakit. Persfektif Pembelajaran dan Pertumbuhan, meningkatkan keterampilan dan kinerja karyawan.